At what age are English Premier League players at their most productive? A case study investigating the peak performance years of elite professional footballers - Jamil, M.; Kerruish, S. (International Journal of Performance Analysis in Sport, 2020)
Seasonal statistics for 637 professional football players performing in the English Premier League (EPL) across 3 intermittent seasons were analysed via a series of Kruskal-Wallis tests in order to determine the most productive (peak) years of players` careers. Contrary to previous research, results revealed that age had no bearing on the technical performance levels of goalkeepers, full-backs, central defenders or central midfielders performing in the EPL. Wingers aged between 16-20 and 21-25 have significantly more shots on target (p = 0.022, p = 0.040) and more attempts from open play (p = 0.012, p = 0.028) than wingers over the age of 26. Results also revealed that strikers aged between 21 and 25 are more adept at executing specific attacking actions such as scoring goals from outside the box (p = 0.024) and shooting on target from outside the box (p = 0.021) than older strikers aged between 26 and 30. Evidence is discovered proving that ageing trends are present but not uniform across the sport of football. The authors conclude that further league specific case studies are required in order to identify the unique characteristics and peculiarities of foreign leagues enabling a more objective approach to recruitment decisions and individualised coaching plans.